99Mo and 67Cu isotope yields under production conditions of NSC KIPT electron accelerator KUT-30 - Aizatsky, N.I.; Diky, N.P.; Dovbnya, A.N.; Ehst, D.; Lyashko, Yu.V.; Nikiforov, V.I.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Shevchenko, V.A.; Shramenko, B.I. (Національний науковий центр «Харківський фізико-технічний інститут» НАН України, 2010)
Computer simulation has been used to determine the 99Mo and 67Cu isotope yields, as well as the radiation power absorbed in technological natural Mo- and Zn-based targets of different mass and geometry, and also, the power absorbed in a tantalum converter versus the converter thickness and spatial-energy characteristics of the electron beam from the accelerator KUT-30 (energy up to 45 MeV, average beam current up to 300 μA). The results of experimental studies are in good agreement with the simulation data.